Brief Report: Hydroxychloroquine does not induce hemolytic anemia or organ damage in a “humanized” G6PD A- mouse model - Benjamin E. Zuchelkowski; Ling Wang; Sebastien Gingras; Qinzi Xu; Minying Yang; Darrell Triulzi; Grier P. Page; Victor R. Gordeuk; Daniel B. Kim-Shapiro; Janet S. Lee; Mark T. Gladwin; Patrick G. Gallagher (PLoS ONE, 2020)
Background Hydroxychloroquine (HCQ) is widely used in the treatment of malaria, rheumatologic disease such as lupus, and most recently, COVID-19. These uses raise concerns about its safe use in the setting of glucose-6-phosphate dehydrogenase (G6PD) deficiency, especially as 11% of African American men carry the G6PD A- variant. However, limited data exist regarding the safety of HCQ in this population. Study design and methods Recently, we created a novel “humanized” mouse model containing the G6PD deficiency A- variant (Val68Met) using CRISPR technology. We tested the effects of high-dose HCQ administration over 5 days on hemolysis in our novel G6PD A- mice. In addition to standard hematologic parameters including plasma hemoglobin, erythrocyte methemoglobin, and reticulocytes, hepatic and renal function were assessed after HCQ. Results Residual erythrocyte G6PD activity in G6PD A- mice was ~6% compared to wild-type (WT) littermates. Importantly, we found no evidence of clinically significant intravascular hemolysis, methemoglobinemia, or organ damage in response to high-dose HCQ. Conclusions Though the effects of high doses over prolonged periods was not assessed, this study provides early, novel safety data of the use of HCQ in the setting of G6PD deficiency secondary to G6PD A-. In addition to novel safety data for HCQ, to our knowledge, we are the first to present the creation of a “humanized” murine model of G6PD deficiency.